Synthesis, microstructure and electrical properties of Ti doped SrSnO3 - Singh S.; Singh P.; Parkash O.; Kumar D. (My University, 2025)
Samples in the system SrSn1-x TixO3 were prepared by conventional solid state ceramic route for 0≤x≤0.50. Powder X-ray diffraction was performed to confirm formation of single phase solid solution. It has been found that solid solution forms only up to x=0.40. DC resistivity and Seebeck coefficient α were measured to understand electrical conduction behaviour. It has been observed that in all the compositions electrons are the major charge carriers. Scanning electron micrographs were taken to study the microstructure. It has been found that grain size is in the range of 1-5 μm. Based on the results of α and activation energy Ea of DC conduction, it is proposed that conduction occurs due to migration of O2- ions through oxygen vacancies Vo for all the compositions. © 2007 Institute of Materials, Minerals and Mining.